Families Created by Egg Donation: Parent–Child Relationship Quality in Infancy. Issue 4 (17th July 2018) - Imrie, Susan; Jadva, Vasanti; Fishel, Simon; Golombok, Susan
Abstract : Increasing numbers of children are being born through egg donation and thus do not share a genetic relationship with their mother. Parent–infant relationship quality was examined in 85 egg donation families and a comparison group of 65 in vitro fertilization families (infant M  =   11 months). Standardized interview and observational measures were used to assess mother–infant and father–infant relationship quality at the representational and behavioral levels. Few differences were found between family types in parents' representations of the parent–infant relationship. Differences were found between family types in the observational assessment of mother–infant relationship quality, indicating less optimal interactions in egg donation families. Findings suggest that egg donation families function well in infancy overall, but there may be subtle yet meaningful differences in mother–infant interaction quality.